FTIR, SEM and XRD analysis of activated carbon from sago wastes using acid modification. Issue 1 (July 2021) - Kunusa, W R; Iyabu, H; Abdullah, R
Abstract: Activated charcoal bio adsorbent is a method that can be developed because the raw material is easy to obtain and does not require large costs such as processing sago. The stages of making activated carbon include the stages of dehydration, carbonization, and extraction of silica using 4% NaOH solution (1:10). The activation stage successively used 250 mL of 1M NaCl, 1M MgCl2, 1M CaCO3, 1M K2 Cr2 O7 and the addition of 100 mL of 1M HNO3, 3% H2 O2, 1M H3 PO4 and 4NH2 SO4 respectively. The activation process uses a water bath at 700°C for 3 hours. In the conventional carbonization stage in a vacuum used drum for 1x24 hours. Physicochemical analysis of activated carbon products, namely moisture content, ash content, pH, Activated Carbon Adsorption Test against Iod Test and methylene blue. FT-IR analysis showed a wide band of 3442.94 cm ‒1 to 3415.93 cm ‒1 which showed the free O-H strain vibrations of the OH group in the cellulose molecule. 1178.51 cm ‒1, –1039.53 cm ‒1, -1024.20 cm ‒1, C-C and C-O-C glycosidic ether band. SEM data describes the differences in the surface morphological structure of each sample and is supported by XRD data.